Properties of dispersion and phase index in magnetized one dimensional ferrite photonic crystals in longitudinal configuration for TM mode. (August 2018) - Sharma, Yogesh; Prasad, Surendra
Abstract: The band structure and phase index in magnetized one dimensional ferrite photonic crystals are computed for TM mode in longitudinal configuration using transfer matrix method. The parametric studies are performed to investigate the effect of filling factor, incident angle and external magnetic fields on dispersion and phase index of the considered structure. The variation of frequency and filling factor at fixed normalized parallel wave vector shows that photonic band gaps occur in the form of lobes. The variation of frequency with external magnetic fields at different normalized parallel wave vector shows that effect of the external magnetic fields have strong influence on second and higher order photonic band gaps. The phase index is also found to be sensitive function of filling factor and normalized parallel wave vector. Highlights: Dispersion and phase index properties of magnetized 1-D FPhCs are investigated. The magnetized 1-D FPhCs shows dielectric nature. With increase in the filling factor, phase velocity along interface decreases. The phase index is sensitive function of filling factor and parallel wave vector.